Bahasa Inggris - Gupta, Gede Endy Kumara; I Gusti Ngurah Sudiana; I Gede Sutarya (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2026)
This study examines the diffusion, transformation, and localization of Jyotiṣa, the Vedic science of astronomy and astrology, within the cultural and intellectual landscape of the Nusantara, particularly through its development into Wariga. As one of the six Vedāṅga, Jyotiṣa played a central role in regulating ritual time through astronomical and cosmological calculations. Its transmission to Southeast Asia, primarily through the Śaka calendrical system, occurred alongside broader networks of trade, religious exchange, and cultural interaction between ancient India and the Nusantara. Using a historical-textual and epigraphic approach, this study analyzes Vedic and Wariga texts alongside Javanese and Balinese inscriptions to trace the diffusion and adaptation of Jyotiṣa concepts within the local Pawukon framework. The findings demonstrate that Wariga was not a passive adoption of Vedic knowledge, but a creative reconstruction that integrated the luni-solar Jyotiṣa system with indigenous temporal cycles such as wuku and wewāran. This synthesis produced a hybrid epistemology in which time functions not only as an astronomical measure, but also as an ethical and symbolic construct embedded in the cosmological worldview of Hindu communities in the Nusantara, particularly in Java and Bali. In conclusion, Wariga represents a localized reformulation of Vedic temporal knowledge that sustained both cosmic order and the cultural continuity of Hindu civilization in the Nusantara.